Flatseta, a new genus of Dikraneurini (Hemiptera: Cicadellidae: Typhlocybinae) from China, with description of a new species - Jiao, Meng; Yang, Maofa (Zootaxa, 2015)
Flatseta gen. n. described and illustrated based on type species F. scimitara sp. n. from China and placed in the typhlocybine tribe Dikraneurini. The new genus is unique among known Typhlocybinae in having modified setae distributed over the male pygofer appendage. Detailed morphological descriptions and illustration of the new genus are provided.